Peningkatan Keinovatifan Guru Melalui Penguatan Efikasi Diri Dan Kepemimpinan Visioner Kepala Sekolah - Asep Suhendar; Rita Retnowati; Ikhsan Ikhsan (JURNAL MANAJEMEN PENDIDIKAN, 2022)
INCREASING TEACHER INNOVATIVE THROUGH STRENGTHENING SELF-EFFICIENCY AND VISIONER LEADERSHIP OF SCHOOL PRINCIPLESThis study aims to see that the teacher innovation can be improved by examining the relationship between teacher innovativeness and the variables of self-efficacy as well as visionary leadership of school principals. The study was conducted on PNS teachers at SMP Negeri Sub Rayon Sukaraja, Sukabumi Regency with a population of 153 and a sample of 111 people. The study was conducted by using correlational statistical methods in order to determine whether the variables of self-efficacy and visionary leadership of school principals have a positive relationship with innovation. The study resulted in three conclusions; 1) there was a positive and significant relationship between the self-efficacy variable and teacher innovativeness with correlation coefficient (ry1) of 0.5293 and a coefficient of determination (r2y1) of 0.2802, 2) there was a positive and significant relationship between the leadership variables visionary principals with teacher innovativeness with a correlation coefficient (ry2) of 0.4579 and a coefficient of determination (r2y2) of 0.2097, 3) there was a positive and significant relationship between the self-efficacy variable (X1) and the principal's visionary leadership (X2) in general together with teacher innovativeness (Y) with a correlation coefficient (ry12) of 0.5583 and a coefficient of determination (r2y12) of 0.3116. It means that self-efficacy and visionary leadership of school principals have an effect on increasing teacher innovativeness.teacher innovativeness; self-efficacy; visionary leadership